Effectiveness of an image analyzing AI-based Digital Health Technology to identify Non-Melanoma Skin Cancer and other skin lesions: results of the DERM-003 study - Marsden, Helen; Morgan, Caroline; Austin, Stephanie; DeGiovanni, Claudia; Venzi, Marcello; Kemos, Polychronis; Greenhalgh, Jack; Mullarkey, Dan; Palamaras, Ioulios (Frontiers in Medicine, 2023)
Identification of skin cancer by an Artificial Intelligence(AI)-based Digital Health Technology could help improve the triage and management of suspicious skin lesions. The DERM-003 study (NCT04116983) was a prospective, multi-centre, single-arm, masked study that aimed to demonstrate the effectiveness of an AI as a Medical Device (AIaMD) to identify Squamous Cell Carcinoma (SCC), Basal Cell Carcinoma (BCC), pre-malignant and benign lesions from dermoscopic images of suspicious skin lesions. Suspicious skin lesions that were suitable for photography were photographed with 3 smartphone cameras (iPhone 6S, iPhone 11, Samsung 10) with a DL1 dermoscopic lens attachment. Dermatologists provided clinical diagnoses and histopathology results were obtained for biopsied lesions. Each image was assessed by the AIaMD and the output compared to the ground truth diagnosis. 572 patients (49.5% female, mean age 68.5 years, 96.9% Fitzpatrick skin types I-III) were recruited from 4 UK NHS Trusts, providing images of 611 suspicious lesions. 395 (64.6%) lesions were biopsied; 47 (11%) were diagnosed as SCC and 184 (44%) as BCC. The AIaMD AUROC on images taken by iPhone 6S was 0.88 (95% CI: 0.83-0.93) for SCC and 0.87 (95% CI: 0.84-0.91) for BCC. For Samsung 10 the AUROCs were 0.85 (95% CI: 0.79-0.90) and 0.87 (95% CI: 0.83-0.90), and for the iPhone 11 they were 0.88 (95% CI: 0.84-0.93) and 0.89 (95% CI: 0.86-0.92) for SCC and BCC, respectively. Using pre-determined diagnostic thresholds on images taken on the iPhone 6S the AIaMD achieved a sensitivity and specificity of 98% (95% CI: 88-100%) and 38% (95% CI: 33-44%) for SCC; and 94% (95% CI: 90-97%) and 28% (95 CI: 21-35%) for BCC. All 16 lesions diagnosed as melanoma in the study were correctly classified by the AIaMD. The AIaMD has the potential to support the timely diagnosis of malignant and premalignant skin lesions.